2015
DOI: 10.1515/pjvs-2015-0023
|View full text |Cite
|
Sign up to set email alerts
|

The splenocyte proliferative response and cytokine secretion in mice after oral administration of commercial gold nanocolloid

Abstract: Owing to their unique physicochemical properties, gold nanoparticles find numerous biomedical applications. Experiments on rodents prove that the main target organs of gold nanoparticles entering an organism are the liver and spleen, whose reticuloendothelial system removes foreign particles from the bloodstream. Through interactions with resident tissue macrophages, nanoparticles can evoke a systemic immunological response.The aim of this study has been to determine the effect of oral administration of commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In an in vivo study using mice, orally administered GNP were able to differentially affect ex vivo lymphocyte proliferative responses-stimulatory at low doses and inhibitory at high doses (Małaczewska 2015). Dose-dependent increases in proliferative indices for CD3 þ and CD4 þ T-cells and no change in CD8 þ Tcells were seen in human PBL treated in vitro with GNP (12 nm diameter) at concentrations of 1-25 lg/ml (Guevel et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In an in vivo study using mice, orally administered GNP were able to differentially affect ex vivo lymphocyte proliferative responses-stimulatory at low doses and inhibitory at high doses (Małaczewska 2015). Dose-dependent increases in proliferative indices for CD3 þ and CD4 þ T-cells and no change in CD8 þ Tcells were seen in human PBL treated in vitro with GNP (12 nm diameter) at concentrations of 1-25 lg/ml (Guevel et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the data showed a time- and dose-dependent influence of GNPs on splenocytes. The lowest dose had a pro-inflammatory effect and stimulated the synthesis of proinflammatory cytokines including IL-1β, IL-6, and TNF-α [ 116 ]. However, some studies reported contradictory results [ 75 , 117 ].…”
Section: Gold Nanoparticles For Immune Stimulation; Focus On Anti-inflammatory and Antioxidant Propertiesmentioning
confidence: 99%
“…Further, in vivo GNP effects are dose-dependent. In particular, Małaczewska 59,60 demonstrated that mice, after being orally administered with GNPs, showed an increased activity of phagocytes and some changes in the lymphocyte phenotypes, i.e. , an increased percentage of B and CD4+/CD8+ double positive T cells.…”
Section: Interaction Of Gold Nanoparticles With Immune Cellsmentioning
confidence: 99%